HUMAN RESOURCE PRACTICES OF SELECTED TELECOMMUNICATION COMPANIES FOR STRATEGIC POSITIONING IN THE POST-COVID ERA - Lorena B. Bondoc; Renalyn C. Estiller (PUPIL: International Journal of Teaching, Education and Learning, 2026)
The primary purpose of this research is to synthesize existing literature to develop Human Resource (HR) strategies for selected telecommunication companies in the post-COVID era. To achieve this, the study uses a qualitative meta-analysis approach, specifically employing meta-ethnography and thematic synthesis. This methodology enables interpretation of findings beyond individual studies, fostering the development of new theoretical frameworks relevant to human resource management. The research investigates six key HR functions: recruitment and selection, onboarding process, compensation and benefits, training and development, performance management, and retirement. It analyzes their evolution across four distinct periods: the 1990s, 2000s, 2010s, and the post-COVID digital era. The study also addresses the continuous changes and disruptions driven by digitalization, including the Digital Eras 4.0 and 5.0. This qualitative meta-analysis examines the historical evolution of Human Resource practices in global telecommunications companies, focusing on their impact on managers' performance and motivation. The study chronicles the shift from traditional personnel administration in the early 20th century to a modern, strategic HR paradigm in the post-COVID digital era. The analysis is anchored in foundational theories, including Maslow's Hierarchy of Needs, Herzberg's Two-Factor Theory, and Vroom's Expectancy Theory. It reveals a profound shift from a focus on basic control and efficiency to a strategic Human Resource Management model that emphasizes employee experience, digital integration, and continuous skill development. The findings highlight how evolving HR practices influence a manager's motivation and performance throughout their career. The report also identifies a significant research gap in the existing literature, which often fragments the historical narrative of HR practices and overlooks the unique experiences of managers in this specific industry. This dissertation's key contribution is the development of a novel conceptual framework for strategic HR positioning. This framework is designed to help organizations optimize their human resource management to enhance performance and resilience. By synthesizing existing research, the study provides actionable insights for HR leaders and executives, helping them navigate talent management’s complexities and maintain a competitive advantage in the dynamic, post-COVID telecommunications sector.